Catalytic Cracking of Lactide and Poly(Lactic Acid) to Acrylic Acid at Low Temperatures. Issue 9 (20th April 2017) - Terrade, Frédéric G.; van Krieken, Jan; Verkuijl, Bastiaan J. V.; Bouwman, Elisabeth
Abstract: Despite being a simple dehydration reaction, the industrially relevant conversion of lactic acid to acrylic acid is particularly challenging. For the first time, the catalytic cracking of lactide and poly(lactic acid) to acrylic acid under mild conditions is reported with up to 58 % yield. This transformation is catalyzed by strong acids in the presence of bromide or chloride salts and proceeds through simple SN 2 and elimination reactions. Abstract : Sweet diapers ! A radical new and efficient synthetic method is presented, which converts lactide to acrylic acid in a convenient one‐pot/one‐step process. Acrylic acid is a highly valued chemical and a starting material for superabsorbent polymers (SAPs), which finds their prime application in diapers. The technique presented here is an important step towards full biobased SAPs and turns lactide into a key platform chemical in the biobased arena.